Circumcision Complications Associated with the Plastibell Device and Conventional Dissection Surgery: A Trial of 586 Infants of Ages up to 12 Months - Seyed Abdollah Mousavi; Ebrahim Salehifar (Advances in Urology)
Conventional dissection surgery (CDS) or using the Plastibell device (PD) is the method most frequently employed for circumcision. The aim of this study was to evaluate two methods in terms of the incidence of complications in infants of ages up to 12 months. In a prospective study, 586 infants equal to or less than 12 months were studied from 2002 to 2008, and complications between the two groups were assessed. The overall rates of complications in CDS and PD groups were 1.95% and 7.08%, respectively. In each group, the rate of complications was not different among children who had a normal weight, compared to those of a lower or upper (10%) weight. There was a significant positive correlation between the age and weight of subjects within the time of ring separation (𝑃<.001). The results of this study suggest the PD method for neonates and low-weight infants with thin prepuce and the CDS for other infants.